LITERATURE REVIEW: PERAN CAREER DEVELOPMENT DALAM MENINGKATKAN WORK ENGAGEMENT DOSEN - Muchtadin Muchtadin; Veithzal Rivai Zainal; Setyo Riyanto; Mafizatun Nurhayati (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Work engagement is one of the crucial aspects that a lecturer must possess. This research aims to provide an overview of the relationship between career development and work engagement among employees, including lecturers. The references for this study were obtained from Google Scholar, with specific criteria spanning from 2014 to 2023, focusing on work engagement dimensions of vigor, dedication, and absorption. The research findings indicate variations in the connection between career development and work engagement. These differences are believed to be attributed to organizational support and length of service factors. Over the past decade, no significant association has been found between career development and work engagement among lecturers in Indonesia.